Wage Growth and the Theory of Turnover - Munasinghe, Lalith (Journal of Labor Economics, 2000)
Theories of turnover and wage dynamics have studied the impact of wage levels on turnover, but they have failed explicitly to model the role of wage growth in predicting turnover. This article presents a theory of turnover that explains why within‐job wage growth reduces the likelihood of worker‐firm separations. The model determines the evolution of value among jobs that differ systematically in permanent rates of wage growth and shows that the value of high wage‐growth jobs increases faster. With additional assumptions about the search process, this proposition implies that high wage‐growth jobs are less likely to end.